Ethical Practices in Purchasing - Laura B. Forker; Robert L. Janson (Journal of Purchasing and Materials Management, 1990)
Uncertainty about what constitutes ethical conduct has increased markedly for purchasing people in recent years. This article reports the results of a study that was conducted jointly by Ernst & Whinney and NAPM's Center for Advanced Purchasing Studies, with support from Purchasing World magazine. Thirty-nine states, the District of Columbia, and Canada were represented among the survey respondents. The questionnaire utilized in the study requested detailed information in the following areas: (1) ethical practices, (2) buying experience, (3) acceptance of favors, (4) narrative comments, (5) organizational profile, and (6) personal data about the respondent. The results of the study were compared with those received from a similar regional study conducted in 1975 by Ernst & Whinney and also with the results of a 1978 purchasing ethics study conducted by the Illinois Institute of Technology. The current study indicates that the vast majority of purchasing personnel conduct their business affairs in an ethical manner; however, they do not agree on how ethical standards can be enforced. Adoption of a formal ethics policy is considered helpful in preventing dubious practices, but respondents report that today top management is issuing fewer policy statements concerning ethical standards of conduct than it did twelve years ago.
Keywords: 650; Ethical practices; Purchasing